Small clause predicates and sluicing - Stockwell, R (Cambridge University Press, 2023)
This Commentaire bears out a prediction of Anand et al.'s (to appear) syntactic identity condition on sluicing. Identity is calculated over argument domains as small as small clauses. With extraction of a small clause subject, sluicing is possible where only a small clause predicate has an antecedent.